2021
DOI: 10.1093/jscr/rjab436
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral renal fungal bezoars in a preterm infant: case report and literature review

Abstract: Renal fungal bezoars or fungal balls is a rare condition in neonates and infants, usually occurring in immunocompromised patients. Renal bezoars result from accumulations of fungal cells and renal epithelial cells. The most common manifestation is candiduria, which can cause urinary tract obstruction. The treatment of choice is prompt medical or surgical intervention, as indicated to eliminate the infection and preserve renal function. Herein we report the case of a 34-week preterm male infant who presented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“… 20 Ultrasound shows the bezoars as a hyperechoic lesion on renal or bladder ultrasonography. 10 , 21 As in our case, a non-contrasted CT scan could show the fungal balls as low density lesions which might resemble urinary stones and may be reported mistakenly as such. 12 However, as in other reported cases, a CT scan might only show hydronephrosis, fatty stranding around the kidney, and rarely air bubbles without an identifiable lesion of the bezoar, in such cases, a CT scan with an excretory phase can identify the bezoars as filling defects.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“… 20 Ultrasound shows the bezoars as a hyperechoic lesion on renal or bladder ultrasonography. 10 , 21 As in our case, a non-contrasted CT scan could show the fungal balls as low density lesions which might resemble urinary stones and may be reported mistakenly as such. 12 However, as in other reported cases, a CT scan might only show hydronephrosis, fatty stranding around the kidney, and rarely air bubbles without an identifiable lesion of the bezoar, in such cases, a CT scan with an excretory phase can identify the bezoars as filling defects.…”
Section: Discussionsupporting
confidence: 54%
“… 3 , 5 , 9 Fungal balls could be also directly extracted using flexible ureteroscopy, cystoscopy, PCNL, or by surgical exploration in more complicated cases. 10 - 14 ,21,22 In our case, the treatment of the fungal balls with a systemic antifungal agent (fluconazole) was sufficient enough for a complete eradication of an extensive fungal bezoar infection that was extending through the calyceal systems, ureters, and urinary bladder.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Renal fungal bezoars may be a cause of renal insufficiency, especially in paediatric patients 5. There are even reports about bilateral renal fungal bezoars in infants causing acute kidney failure 6. Das et al reported a case series of two patients who underwent percutaneous lithotomy for bilateral radiolucent staghorn calculi, but pathology revealed the presence of fungal bezoars, and the patients were eventually treated with antifungal agents 7.…”
Section: Discussionmentioning
confidence: 99%